Study the Effect of Alternaria Toxins (AAL) on Root Tip Cells of Vicia faba - Abogharsa, I. A.; Khattab, H. A.; El-Maleh, A. A. (Al-Mukhtar Journal of Sciences, 2008)
The aim of this study to isolate the toxins of Alternaria alternate F. Sp. Ycopersiei (AAl) from tomato plant, and study their effect on chromosomes of a very sensitive eukaryotic eukaryotic organism (Vicia faba) to chemical toxins. The results of the effect of these toxins on tested plant indected that decreased in mitotic index, produced excessive condensation of pro-and metaphase chromosomes, and caused an accumulation of metaphase, in addition to chromosome stickiness and low frequencies of chromosomal aberrations as well as induced micronuclei chromosome breaks.